Q: PLEASE HELP THANKS: (4x – 3.5) – (3x + 1.7)

A: (4x – 3.5) – (3x + 1.7) = 4x - 3x - 3.5 - 1.7; = x - 5.2

selymi|Points 1682|

Question

Asked 3/21/2011 8:50:20 PM

Updated 280 days ago|9/14/2017 5:33:08 PM

1 Answer/Comment

This conversation has been flagged as incorrect.

Flagged by alfred123 [9/14/2017 5:33:08 PM]

Rating

3

(4x – 3.5) – (3x + 1.7)

= 4x - 3x - 3.5 - 1.7;

= x - 5.2

= 4x - 3x - 3.5 - 1.7;

= x - 5.2

Added 280 days ago|9/14/2017 5:33:05 PM

This answer has been confirmed as correct and helpful.

Confirmed by jeifunk [9/14/2017 6:15:58 PM]

Could you please simplify (5x^2y)^3 Thank you

Question

Not Answered

Updated 8/17/2014 8:09:54 PM

1 Answer/Comment

(5x^2y)^3 = 125x^6y^3

Added 8/17/2014 8:09:54 PM

This answer has been confirmed as correct and helpful.

Add.
(-3 + 8x5 + 3x7 + 8x6) + (-2x6 - 6x5 - 6 + 8x7) **Weegy:** It would be the first one x=3 **User:** Subtract.
(3x3 + 2x5 - 1 + 7x4) - (5 + 9x4 + 9x5 - 5x3)
Which one is the correct answer: 11x5 + 16x4 - 2x3 + 4, or -7x5 - 2x4 + 8x3 – 6, or -7x5 + 16x4 - 2x3 + 4, or 11x5 + 16x4 - 2x3 – 6?
(More)

Question

Expert Answered

Updated 1/28/2014 8:51:25 AM

2 Answers/Comments

(-3 + 8x^5 + 3x^7 + 8x^6) + (-2x^6 - 6x^5 - 6 + 8x^7)

= 11x^7 + 6x^6 + 2x^5-9

= 11x^7 + 6x^6 + 2x^5-9

Added 1/28/2014 8:50:28 AM

This answer has been confirmed as correct and helpful.

(3x^3 + 2x^5 - 1 + 7x^4) - (5 + 9x^4 + 9x^5 - 5x^3)

= -7x^5 -2x^4 + 8x^3 - 6

= -7x^5 -2x^4 + 8x^3 - 6

Added 1/28/2014 8:51:25 AM

This answer has been confirmed as correct and helpful.

Given the expression x^6 + x^8 + x^3. What is the degree of the polynomial? **Weegy:** degree is 3 since its the highest exponent. (More)

Question

Expert Answered

Updated 7/18/2014 7:34:21 AM

2 Answers/Comments

The degree of the polynomial is 8. It is the highest degree of any term in the polynomial.

Added 7/18/2014 7:34:18 AM

This answer has been confirmed as correct and helpful.

(4x + 1)(x^2 – 9x + 5)
**Weegy:** 4x3-35x2+5 (More)

Question

Expert Answered

Updated 170 days ago|1/2/2018 6:36:29 PM

1 Answer/Comment

(4x + 1)(x^2 – 9x + 5)

= 4x^3 + x^2 - 36x^2 - 9x + 20x + 5

= 4x^3 - 35x^2 + 11x + 5

= 4x^3 + x^2 - 36x^2 - 9x + 20x + 5

= 4x^3 - 35x^2 + 11x + 5

Added 170 days ago|1/2/2018 6:36:28 PM

This answer has been confirmed as correct and helpful.

(5x^2 + 3x) + (2x + 5)

Question

Expert Answered

Updated 5/24/2015 8:09:53 AM

1 Answer/Comment

(5x^2 + 3x) + (2x + 5)

= 5x^2 + 2x + 3x + 5

= 5x^2 + 5x + 5

= 5x^2 + 2x + 3x + 5

= 5x^2 + 5x + 5

Added 5/24/2015 8:09:53 AM

This answer has been confirmed as correct and helpful.

27,009,444 questions answered

There are no comments.